Diagnostic Value of the Online Stroop Test in Assessing Cognitive Functions - Khusnidinov Firdavs (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article examines the Stroop test and its online version as an important tool in psychology and neuropsychology. The test allows assessment of the level of cognitive control, selective attention, and the ability to suppress interference. With the development of digital technologies, online versions of the test have become widely used, significantly simplifying research and diagnostic procedures. The article analyses the principles underlying the test, its advantages and limitations, as well as its fields of application in medicine and psychology.